Correlation between trans and intra-thoracic impedance and conductance in patients with chronic heart failure. Issue 4 (April 2016) - Malfatto, Gabriella; Villani, Alessandra; Rosa, Francesco Della; Rella, Valeria; Oldani, Matteo; Giglio, Alessia; Facchini, Mario; Parati, Gianfranco
Abstract : Aims: In chronic heart failure, changes of intra-thoracic impedance (Z0IT ) may suggest impending pulmonary congestion; a similar result has been found by measuring trans-thoracic conductance (TFCTT = 1/Z0 = 1/kΩ). We assumed that a relationship could exist between Z0IT and TFCTT . Methods: We collected 140 measurements from 70 patients carrying an implantable cardioverter-defibrillator/cardiac resynchronization device with the CareLink function (71 ± 9 years, New York Heart Association (NYHA) 2.4 ± 0.9, ejection fraction 31 ± 8%, optimal treatment); they were studied during system alarms and after appropriate treatment (diuretics and/or vasodilators, n = 42) or during clinical stability and at the time of a system alarm ( n = 28); correspondent BNP values were obtained. We related Z0IT obtained by the device, with TFCTT obtained with a commercial system. Results: A strong relationship was found between Z0IT and TFCTT . Changes in the variables after treatment or during worsening conditions were of the same direction and order of magnitude, and were related to BNP levels obtained simultaneously. Conclusions: Trans-thoracic conductance, similarly to intra-thoracic impedance, may noninvasively point to pulmonary congestion and be useful in patients not carrying an implanted device. The possibility of remotely obtaining this variable should be evaluated for the telemonitoring of heart failure patients.